The Influence of Information Technology Competence and Educational Level on Work Productivity at the University - Winarno, Winarno; Indrawati, Cicilia Dyah Sulistyaningrum; Ninghardjanti, Patni; Subarno, Anton (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The competence of educational staff in information technology is essential to finishing a job at a university. Good information technology competence can help them complete the work faster and more effectively. This study investigates the influence of communication competence and education level on work productivity at Sebelas Maret University. Two hundred ten respondents were involved, consisting of 125 male and 85 female staff. Pearson correlation is used for validation, and Cronbach's alpha is used for reliability tests. All items are valid and reliable (α =.05.) The data were analyzed using multiple linear regressions. The result shows that simultaneously, the two independent variables have a significant effect on the dependent variable (F = 9.63, p <.05). Information technology competence has a significant effect on work productivity (t = 4.64, p <.05). Education level has a significant effect on work productivity (t = 2.48, p <.05). Generally, it can be concluded that the information technology competence and educational level of staff affect work productivity.